Knowledge-Qua in Groups - Jesper Kallestrup (Ergo, An Open Access Journal of Philosophy, 2025)
Deflationism about group knowledge is the view that a group has knowledge if and only if most of its members have that knowledge. The case against deflationism has revolved around epistemic divergence arguments, which typically aim to show that members’ knowledge isn’t necessary for group knowledge. This paper is instead devoted to objections against members’ knowledge being sufficient for group knowledge. Focusing on structured groups in which members occupy roles that are connected by internal links in a social network, we develop a notion of knowledge qua such occupancy. We proceed to argue that if deflationists adopt such knowledge-qua as what constitutes structured group knowledge, they have the resources to counter worries about the sufficiency condition. If instead groups are taken to be feature collectives, then similar worries are much less pressing. Finally, we elaborate on the societal function of knowledge-qua, as well as the different epistemic assessments that arise, depending on whether the role or its occupant is considered.